Corporate Performance Pressure, Goodwill and Corporate Social Responsibility - et. al., Hua Jiang , (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Nowadays, how enterprises coexist harmoniously with the society has become an issue that enterprises, governments, and scholars are paying more and more attention to. The fulfillment of corporate social responsibility has also become an inevitable choice for enterprises. It is especially important to understand its influencing factors so as to improve the fulfillment of Corporate Social Responsibility. Based on the theory of Corporate Social Responsibility, this paper constructs a research framework. By commenting on relevant theories, based on the review of domestic and international research, methods of literature analysis and quantitative analyses have been used to research the relationship between “Corporate Performance Pressure” and “Corporate Social Responsibility”. It also explores the role of “Goodwill” in moderating the relationship between “Corporate Performance Pressure” and “Corporate social responsibility”. The study found that there is a significant negative correlation between “Corporate Performance Pressure” and “Corporate Social Responsibility”, that is, the greater the “Corporate Performance Pressure”, the lower the Corporate Social Responsibility rating; in the case of good reputation, its effect on enhancing the negative relationship between “Corporate Performance Pressure” and “Corporate Social Responsibility” is much more remarkable. The conclusions of this study have certain significance for the existing management practice, and promote the new thinking of the regulatory departments and stakeholders on the performance pressure of enterprises. The previous research focused on the current period and selected “Financial Performance” to study its impact on “Corporate Social Responsibility”. Based on the expectation, this paper selects “Corporate Performance Pressure” as the explanatory variable which is relatively innovative, enriching the relevant literature on the factors affecting corporate social responsibility and providing a corresponding reference for scholars to study Corporate Social Responsibility from a multi-dimensional perspective.